2003
DOI: 10.1136/aim.21.1-2.18
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Soft Tissue Shoulder Disorders: A Series of 201 Cases

Abstract: A retrospective observational study was performed on shoulder pain cases seen in a community general practice. Two hundred and one patients were treated with acupuncture (on distant points plus local shoulder points), moxibustion and auriculotherapy. Data was retrieved from records over a three-year period to assess the effect of acupuncture and moxibustion on pain, mobility and disability, and to compare perceived efficacy rates with published reports from Chinese acupuncturists. Using a four-point outcome sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Although auricular somatotopic mappings may not be based on or supported by any medical or scientific evidence, auriculotherapy is commonly used to treat patients with substance abuse and musculoskeletal pain. [2][3][4][5][6] The stimulation techniques applied to the external auricle are similar to those used for acupuncture treatment. As a result, auriculotherapy is commonly considered a microsystem acupuncture therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Although auricular somatotopic mappings may not be based on or supported by any medical or scientific evidence, auriculotherapy is commonly used to treat patients with substance abuse and musculoskeletal pain. [2][3][4][5][6] The stimulation techniques applied to the external auricle are similar to those used for acupuncture treatment. As a result, auriculotherapy is commonly considered a microsystem acupuncture therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Williamson et al randomised 102 adult patients with hayfever and compared acupuncture with an invasive sham technique involving superficial needling over the middle of the patella. 1 In this trial both groups improved substantially, with no difference between them. Some time ago I was talking to Lyn Williamson about her trial, and she mentioned that in her old practice there were still some patients requesting the 'special knee acupuncture' to treat their hayfever symptoms each year, since it had apparently been so successful for them during the trial.…”
Section: Discussionmentioning
confidence: 60%
“…Vas et al reported a large case series (n=563) of acupuncture for OA knee in that issue. 1 In the above trial, the electroacupuncture was applied to local knee points: Xiyan (eyes of the knee), ST36, GB34, SP9; and de qi was elicited by manual needling at distant points: ST40, SP6, KI3 and LI4. The treatment period lasted for a total of 12 sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Disorders of the shoulder muscles and tendons (rotator cuff) are thought to be the most common causes of the pain [2]. The true prevalence is unknown, varying in different reports from 4 to 34% [3]. The conventional treatments for shoulder pain are NSAIDs, physiotherapy, cortisone injections and ‘wait and see’ [4,5].…”
Section: Introductionmentioning
confidence: 99%